2021
DOI: 10.1039/d1fo02293h
|View full text |Cite
|
Sign up to set email alerts
|

Probing the conjugation of epigallocatechin gallate with β-lactoglobulin and its in vivo desensitization efficiency

Abstract: Epigallocatechin gallate (EGCG) and β-lactoglobulin (βLg) were conjugated by covalent bonds to form a EGCG-βLg conjugates. This conjugation causes structural and bioactivity changes in βLg, which in turn can be...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Intrinsic fluorophores, namely tryptophan, tyrosine and phenylalanine, exhibit strong fluorescence characteristics at a certain excitation wavelength (Jiang et al ., 2018). When the ligand is accessible to proteins, resonance energy transfer occurs, and the fluorescence emission of these residues is quenched (Ren & Giusti, 2021; Zhang et al ., 2021b). Equation (3) was used to compute Ka (Zhang et al ., 2017): logF0FF=logKa+nlogD where F 0 and F are the fluorescence intensities of the protein at the maximum emission wavelength in the absence and presence of the ligand respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrinsic fluorophores, namely tryptophan, tyrosine and phenylalanine, exhibit strong fluorescence characteristics at a certain excitation wavelength (Jiang et al ., 2018). When the ligand is accessible to proteins, resonance energy transfer occurs, and the fluorescence emission of these residues is quenched (Ren & Giusti, 2021; Zhang et al ., 2021b). Equation (3) was used to compute Ka (Zhang et al ., 2017): logF0FF=logKa+nlogD where F 0 and F are the fluorescence intensities of the protein at the maximum emission wavelength in the absence and presence of the ligand respectively.…”
Section: Resultsmentioning
confidence: 99%
“…All protein fluorescence spectroscopy analyses were performed using a Cary Eclipse Fluorescence Spectrometer (Varian, Bromma, Sweden) according to the method of Zhang et al . (2021b). βLG solution (0.1 m m ) and C3G (0.2 m m ) were mixed and incubated at 20 °C for 2 h in the presence and absence of ultrasound.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DPPH scavenging activity of the samples was measured according to a modified version of a previous method that 0.4 mL of 0.1 mM βLg or its 0.1 mM conjugates mixed with 3.6 mL of 0.1 mM ethanolic DPPH solution (Zhang, Li, Shao, et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The structural, functional and nutritional properties of proteins could be modified by covalent binding to phenolics (Sui et al ., 2018). Our previous study showed that the conjugation of EGCG to βLg affected the Immunoglobulin E (IgE) sites of βLg leading to desensitisation while enhancing antioxidant capacity of βLg by introducing hydroxyl groups of EGCG (Zhang et al ., 2021). Meanwhile, the complex conjugation, which is influenced by many factors, is found to be highly dependent on the structures of phenolics and reaction conditions, especially temperature, leading to low conjugation efficiency (Zhang, Li, Shao, et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%